POTENSI CADANGAN KARBON PADA LAHAN MINERAL PERKEBUNAN KELAPA SAWIT PT. GUNA DODOS KABUPATEN PELALAWAN PROVINSI RIAU - Hidayat Pratamasari; Yusni Ikhwan Siregar; Mubarak Mubarak (Program Pascasarjana Universitas Riau, 2018)
Indonesia's forest area in 2017 is 93.6 million ha and deforestation in forest area 2017 is 64.3% while the export of palm oil from year to year has increased significantly.it can be seen from the average growth rate of palm oil area during 2004 - 2014 is 7.67%.and palm oil production increased on average of 11.09% per year. The approach of this research is quantitative research conducted using systematic equation of some allometric equations. Observation and data measurement is done directly on the object of research with the eight observation points which also applied as replication. The results of research and data processing of palm oil plant carbon stocks on flat surface and wavy surface are Total carbon stock stored in flat surface is 85.36 ton / ha while total carbon stock in wavy surface is about 82.41ton / ha. The average total carbon stock of the lower plants contained in flat surface are 0.95 ton / ha while for wavy surface is 1.16 ton / ha. The Average total understorey carbon stock found on flat surfaces are 1.06 ton / ha while for wavy surface is 1.28 ton / ha. The average total carbon stock of soil contained in flat surface and wavy surface is 0.0031 ton / ha. The average total carbon stock of palm oil plantations in flat surface is 79.73 ton / ha while for wavy surface is 83 ton / ha. While The value of carbon sequestration benefits from the development of palm oil plantation in PT. Guna Dodos Pelalawan Regency is Rp.Rp.10.206.380.810,-.